The Effect of Memory Games Therapy on the Cognitive Function of Older Adults - Basuki, Hyan Oktodia; Oktafia, Siti Herlinda; Suhartono; Pitaloka, Dyah; Widyawati, Mei; Hakim, Lukman; Faizah, Hanim Nur; Nurhadi, Mokhamad; Fauziansyah, Ahmad (Babali Nursing Research, 2025)
Introduction: Cognitive function in older adults often declines, particularly affecting short-term memory. Older adults may also experience difficulties in learning new information, adapting to changes, and recognizing people, places, and objects. One approach to improving cognitive function is memory games therapy. This study aims to examine the effect of memory game therapy on the cognitive function of older people. Methods: This research employed a quasi-experimental design using a one-group pre-test and post-test approach. The study was conducted in September 2024 in Tuban Regency. The population consisted of 36 older adults experiencing cognitive decline, and a sample of 33 participants was selected using a purposive sampling technique. The research instrument was the "Memory Card," and cognitive function was measured using the Mini-Mental State Examination (MMSE) questionnaire. Data were analyzed using the Wilcoxon test with a significance level of α = 0.05. Results: Most respondents were female (54.5%), and 63.6% were aged 60–74. Most participants had completed senior high school (42.5%). Before the intervention, 30.3% of respondents had severe cognitive impairment. After the intervention, 45.5% had mild impairment, and 15.2% showed normal cognitive function. Memory games therapy significantly affected cognitive function in older adults (ρ = 0.000). Conclusion: The findings of this study demonstrate the effectiveness of memory game therapy in improving the cognitive function of older adults. Therefore, it is recommended that nurses incorporate memory game therapy as an intervention in Older Adults' Integrated Service Post activities.